Metaphors in Mata Najwa Podcast Episode: “Eklusif, Ganjar Pranowo dan Piala Dunia” | Mata Najwa - mawaddah, suci (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2023)
This research discusses the use of metaphor features in the Podcast Najwa Shihab Episode “Eklusif: Ganjar Pranowo dan Piala Dunia” | Mata Najwa. This podcast is one of the contents of Najwa Sihab's Youtube channel which is the source of data in this study. The purpose of the research is to analyze the characteristics of metaphors used and their relationship with power. This research was conducted using Fairclough's (1992) critical discourse research approach, which views language as a means of power. The research method used was descriptive qualitative. Through this research, the author found six metaphorical expressions from the podcast episode " Eklusif: Ganjar Pranowo dan Piala Dunia” | Mata Najwa. The results of this study show that language not only plays a central role in human life, but language is also created as a tool to control something, change something or make something happen. Other results show that the discourse and communication patterns between Najwa Shihab and Ganjar Pranowo in the podcast exemplify the exercise of power that directly influences people's opinions and behavior in responding to the government's stance of canceling the 2023 World Cup in Indonesia.